Drug-Induced Stuttering: Occurrence and Possible Pathways - Ekhart, Corine; van Hunsel, Florence; van Harten, Peter; van Baarsen, Jeanette; Yingying, Tan; Bast, Bert (Frontiers in Psychiatry, 2021)
Background: Stuttering is a well-known condition that affects mainly children. Often they recover as they get older. However, a drug-induced form of stuttering may occur at any age. The aim of the present study was to detect drugs that have been associated with stuttering and discuss the mechanisms involved. Method: A descriptive study based on reports submitted to the global pharmacovigilance database Vigibase of the WHO was conducted. Results: A total of 3385 reports of dysphemia were retrieved from Vigibase. These reports were contributed by 51 countries. Anti-epileptics, antidepressants, immunosuppressants, antipsychotics and centrally acting sympathomimetics were among the most frequently implicated drugs. Conclusion: A wide variety of drugs has been linked to the occurrence or recurrence of stuttering. Several mechanisms, such as increased dopamine levels, reduction of GABA, anticholinergic properties of drugs or changes in serotonin levels have been associated with the development of drug-induced-stuttering. Paradoxically, agents known to reduce stuttering in some persons may induce it in others.